Effects of the origins of Botrytis cinerea on earthy aromas from grape broth media further inoculated with Penicillium expansum - Morales-Valle, H. (2011)
Earthy “off” aromas from wine and grape juice are highly detrimental to the production of quality grape products. These volatile compounds are produced on grapes by Botrytis cinerea, Penicillium expansum and/or a combination of P. expansum and B. cinerea strains. B. cinerea strains were isolated from different (a) vineyards in Spain and Portugal, (b) grape varieties (c) bunches (i.e., sound and botrytized) and (d) positions in the botrytized bunch (i.e., interior or exterior). A novel Headspace-Phase Microextraction (SPME) followed by Gas Chromatrography/Mass Spectrometry (GCeMS) dedicated to analyze geosmin, methylisoborneol (MIB), 1-octen-3-ol, fenchone and fenchol in grape broth medium was used. Approximately 50% of the B. cinerea strains induced detectable geosmin. One strain accumulated significant amounts of anisoles, demonstrating that this contamination might already occur in the vineyard. Strains from the interior of Cainho grape bunches induced more geosmin and hence it may be possible to reduce this volatile in wine by avoiding using these grapes in case of B. cinerea attack.